Ovarian cancer primary systemic chemotherapy with cyclophosphamide, epirubicin, carboplatin with concomitant intraperitoneal carboplatin - Kaliński, Adam; Staszewski, Andrzej; Szczylik, Cezary; Wcisło, Gabriel; Korniluk, Jan; Sielużycka, Joanna; Nurzyński, Paweł; Kowalski, Piotr; Langiewicz, Przemysław (Contemporary Oncology/Współczesna Onkologia, 1999)
Purpose. Debulking surgery followed by chemotherapy is a standard in ovarian cancer therapy. The aim of our study was estimation of efficacy of the ovarian cancer primary systemic chemotherapy combinig intravenous carboplatin (CBDCA), cyclophosphamide (CTX), epirubicin (EPI) with concomitant intraperitoneal carboplatin. Methods. We have enrolled women with ovarian cancer (FIGO II-IV), 70-90% Karnofsky’s score. Median age was 56 years (range, 38-77 years). They received a modified regimen consisting of: CTX – 600 mg/m 2 i.v., EPI – 50 mg/m 2 , CBDCA – 400 mg/m 2 plus intraperitoneal CBDCA – 30-40% intravenous dose. Median dose of CTX was 877 mg, CBDCA – 603 mg, EPI – 70 mg, intraperitoneal CBDCA – 167 mg. After the surgery all patients received 205 cycles of chemotherapy (median, 6 [range 3-9 cycles] per patient). All investigated women have been assessed with imaging techniques, hematological & biochemical parameters and serum marker – Ca-125 concentration. Toxicity was assessed using the WHO score schedule. Moreover, laparoscopic evaluation of peritoneal cavity was performed when 3 and 6 chemotherapy cycles were completed. Results. In the group of 29 patients we observed: 48% (14) CR, 45% (12) PR and 7% (2) SD. Overall response rate of 93% (27 females) was observed. Among 5 patients with FIGO II – 4 CR and 1 PR, FIGO III-7 CR, 12 PR, 2 SD; FIGO IV-1 CR, 2 PR have been observed. Stabilization was noticed in 2 women after debulking surgery. Median duration of response was 11,9 months (range 1-46+ months). Among the total estimated number of 131 cycles of chemotherapy in 35 cases (27%) haematologic toxicities (4 th WHO degree) have been observed. During thirty cycles G-CSF/GM-CSF support was required. In one case chemotherapy has been stopped because of severe toxicities. Conclusion. These results indicate importance of systemic chemotherapy combined with intraperitoneal chemotherapy in patients with ovarian cancer.